Online Biped Walking Pattern Generation with Contact Consistency - Wenqi Hou; Jian Wang; Jianwen Wang; Hongxu Ma (Institute of Advanced Engineering and Science, 2015)
In this paper, a novel online biped walking gait pattern generating method with contact consistency is proposed. Generally, it’s desirable that there is no foot-ground slipping during biped walking. By treating the hip of the biped robot as a linear inverted pendulum (LIP), a foot placement controller that takes the contact consistency into account is proposed to tracking the desired orbit energy. By selecting the hip’s horizontal locomotion as the parameter, the trajectories in task space for walking are planned. A task space controller without calculating the inversion of inertial matrix is presented. Simulation experiments are implemented on a virtual 5-link point foot biped robot. The results show the effectiveness of the walking pattern generating method which can realize a stable periodic gait cycle without slipping and falling even suffering a sudden disturbance.